Professional Integrity within the Structure of Professional Activity: Psychological and Pedagogical Formation Basis - Nataliya Petrovna GAVRILYUK; Yana Vladimirovna KRYUCHEVA,; Svetlana Nikolaevna SEMENKOVA (Astra Salvensis, 2019)
The article covers the issues related to the process of training students for professional activity. The authors introduce a new term "professional integrity". This term is presented by three interrelated structural components: cognitive, communicative, and behavioral. The psychological and pedagogical basis of professional activity is theoretically justified. Diagnostic tools for the problematic area of professional activity are verified empirically. The sources of difficulties and problems faced by a person in professional activity are found out. The authors identify a correlation among the sources of difficulties of a person in the important life spheres. Psychological and pedagogical recommendations on solving problems related to the formation of professional activity at higher education institutions are developed. The findings can be attractive for teachers, psychologists, postgraduate students interested in problems of starting professional activity.